2011
DOI: 10.1186/1471-2164-12-531
|View full text |Cite
|
Sign up to set email alerts
|

Tandemly repeated DNA families in the mouse genome

Abstract: BackgroundFunctional and morphological studies of tandem DNA repeats, that combine high portion of most genomes, are mostly limited due to the incomplete characterization of these genome elements. We report here a genome wide analysis of the large tandem repeats (TR) found in the mouse genome assemblies.ResultsUsing a bioinformatics approach, we identified large TR with array size more than 3 kb in two mouse whole genome shotgun (WGS) assemblies. Large TR were classified based on sequence similarity, chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 79 publications
5
78
0
Order By: Relevance
“…Moreover, the experimental evidence regarding the functional features of satellite DNA sequences suggest that they are not selectively neutral, supporting "unexpected" nucleotide conservation, which could be a more extensive event than first thought. However, the functional nature of tandem repeats in any genome remains enigmatic because limited tools are available for dissecting and elucidating the functions of repeated DNA, and the assemblies do not cover even the beginning of the regions of constitutive heterochromatin (Komissarov et al, 2011). The sequences of those regions can only be found in whole-genome shotgun contigs, as in Peromyscus maniculatus bairdii, BioProject: 53563, as analyzed in the present study.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, the experimental evidence regarding the functional features of satellite DNA sequences suggest that they are not selectively neutral, supporting "unexpected" nucleotide conservation, which could be a more extensive event than first thought. However, the functional nature of tandem repeats in any genome remains enigmatic because limited tools are available for dissecting and elucidating the functions of repeated DNA, and the assemblies do not cover even the beginning of the regions of constitutive heterochromatin (Komissarov et al, 2011). The sequences of those regions can only be found in whole-genome shotgun contigs, as in Peromyscus maniculatus bairdii, BioProject: 53563, as analyzed in the present study.…”
Section: Resultsmentioning
confidence: 93%
“…However, the landscape of satDNAs can be modified and may differ among species without necessarily changing the monomeric sequence. In recent years, diverse studies have reported the existence of satellite DNA sequences preserved among evolutionarily distant species, indicating possible functional roles (Li and Kirby, 2003;Mravinac et al, 2005;Komissarov et al, 2011). Transcripts from satellite-containing regions have been identified in multiple organisms (Stimpson and Sullivan, 2010), and proteins that interact with those transcripts have been described (Hall et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Major satellite (MaSat) and minor satellite (MiSat) sequences [29] were concatenated into a single sequence and along with the 45S rRNA gene sequence [30] appended into the mm9 reference sequence to build the new reference sequence for mapping.…”
Section: Methodsmentioning
confidence: 99%
“…All three SatDNAs are AT-rich (64 %, MajSat; 67 %, MinSat; 63-65 %, TLCSat) and show sequence uniformity; monomer variation is about 5.6 % for the MinSat (Kipling et al 1994) and less than 5.0 % for the MajSat (Vissel and Choo 1989), although for the latter, a recent bioinformatic analysis did not confirm such high sequence conservation, perhaps a reflection of chromosome specificity (Komissarov et al 2011). Among the three SatDNA families, TLCSat sequences are the least uniform (82 %), perhaps because of its possible spacer role between telomeres and centromeres, a role for which sequence identity may be less critical (Kalitsis et al 2006).…”
Section: Molecular Composition and Organisation Of The Centromeric Rementioning
confidence: 96%